Recession, Mortality, and Migration Bias: A Comment on Arthi et al. (2022) - Yannick Dupraz (Institute for Replication (I4R), 2023)
Vellore Arthi, Brian Beach and W. Walker Hanlon (2022) investigate the effect of the Lancashire Cotton Famine on mortality, accounting for the migration response to the downturn. They use difference-in-differences to estimate the effect of the cotton famine on mortality. To account for the migration response to the cotton famine, they construct a linked dataset giving mortality rates by district of residence during the cotton famine, rather than by district of residence at the time of death. They find that the cotton famine increased mortality in cotton-textile producing districts, and that accounting for migration matters, in the sense that their estimates would have been markedly different had they not accounted for it. I check that ABH results are fully reproducible using their data and code, and that their claims are robust to (1) decreasing the age window for building the linked dataset, (2) modifying the specification and (3) computing different standard errors. The only significant discrepancy in results is that I find stronger effects of the cotton famine when I decrease the age window for building the linked dataset, likely because this reduces measurement errors.
Keywords: 330